Tradisi Magido Bantu: Budaya Tolong-Menolong Masyarakat Mandailing di Jorong Tamiang Ampalu, Kabupaten Pasaman Barat - Hannah, Hannah; Siregar, Yusra Dewi; Susanti, Neila (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This article discusses the Magido Bantu tradition practiced by the Mandailing ethnic group in Jorong Tamiang Ampalu, West Pasaman Regency. This tradition has become a custom that is commonly practiced before a horja (wedding ceremony) is held. This study uses the historical method in four writing steps, namely; heuristics, verification or criticism, interpretation, and historiography, with a cultural approach. The Padri war that occurred to the Mandailing land area led to the migration of the Mandailing ethnic group who had embraced Islam to the Minangkabau region. This migration also brings with it customs and traditions that were previously practiced, one of which is the Magido Bantu tradition. This tradition has its own procession and implementation procedures that are different from the traditions commonly practiced by the Mandailing ethnic group in other regions. The implementation of this tradition has so many positive values in it, including: an attitude of help, mutual respect, deliberation, and so on. This tradition is still being maintained until now, if a horja is not held it will feel less than perfect.